Pengaruh Transformasi Digital terhadap Penghindaran Pajak dan Peran ESG Disclosure sebagai Variabel Moderasi - Rachmalia, Ina Pramitha; Firmansyah, Amrie (Universitas Prasetiya Mulya, 2025)
This study aims to examine the effect of digital transformation on tax avoidance by considering ESG disclosure as a moderating variable among publicly listed companies in Indonesia. The research sample consists of 68 companies selected using a purposive sampling method, with secondary data obtained from the Indonesia Stock Exchange (IDX) for the year 2024. Multiple linear regression analysis was conducted using cross-sectional data through the EViews software. The results show that digital transformation has not been proven to reduce tax avoidance practices, and ESG disclosure does not moderate the relationship between digital transformation and tax avoidance. Practically, this study provides implications for tax authorities to strengthen the integration between ESG reporting and tax reporting systems, ensuring that sustainability initiatives are aligned with fiscal compliance and corporate transparency.